Providing a Live Chat on Online Shopping with End-to-End Encryption - S.K.Manigandan, Mr.; R.Latha, Mrs.; S.MohamedAsik, Mr.; Velmurugan, J; Ramya, D (International Journal of Engineering and Technology, 2018)
In our these days life on-line purchase associated e-commerce website   has changing into   an mandatory  things   in  our  daily  life vogue  since,  it conjointly  have  some  major  issue  like  purchasing  a product  with  unhappy  mode  and   lack  of data  in product  usage.  therefore as to  overcome  these  drawback we  have  a tendency to   have new entranceway referred to as   live chat  in on-line looking. We have a tendency to  will  offer    this  live   chat  in  most   safest  method  exploitation   the   end  to  finish cryptography  methodology , most  of  the  looking can  have  a   live  chat however  they Weren’t   provided   a cut price options and most e-commerce website   don’t   have Chat choices.  We have a tendency to will even enable the client and producer to Share their thoughts.